A qualitative exploration of the educational needs of people living with heart failure: BANDAIDD-Explore study - Caleb Ferguson; Scott William; Sabine Allida; Peter S. Macdonald; Gary Kilov; Clara K. Chow; Anthony Keech (PLoS ONE, 2025)
This is an exploratory qualitative study of cardiovascular clinicians, people living with heart failure (HF), and their caregivers. The aim was to understand the unmet educational needs in self-management for adults living with HF. Four focus groups were conducted face-to-face or via videoconference, recorded, and transcribed verbatim for thematic analysis. A total of 23 participants were recruited and included in analyses (clinicians n = 13; adults with HF n = 7; caregivers n = 3). The focus groups were on average 81 (range 73 to 91) minutes in duration. Seven key themes were identified which were: (i) Understanding and reinforcing the signs and symptoms, self-management, medications, and prognosis and severity of HF; (ii) Providing concise and timely education; (iii) Building trust and relationships; (iv) Accessibility of education to support patient needs; (v) Engaging family members and informal caregivers; (vi) Tailoring education to patients diverse needs; and (vii) Navigating the health system and dealing with continuity of care. There were several unmet educational needs for people living with heart failure and their caregivers. Providing patient-centred education is critical to developing understanding and reinforcing the signs and symptoms, prognosis, and severity of heart failure, to underpin self-management and optimise medication adherence. Clinicians, patients, and their caregivers provided several suggestions for improvement, such as the importance of providing concise and timely education and building trust and relationships between clinicians and patients. Priorities for education improvement were also provided, including regional and rural considerations; engaging informal family caregivers; tailoring to culturally and linguistically diverse and indigenous peoples, navigating the health system and ensuring continuity of care.